Polifarmácia entre idosos do Município de São Paulo - Estudo SABE Polypharmacy among the elderly in the city of São Paulo, Brazil - SABE Study - Maristela Ferreira Catão Carvalho; Nicolina Silvana Romano-Lieber; Gun Bergsten-Mendes; Silvia Regina Secoli; Eliane Ribeiro; Maria Lúcia Lebrão; Yeda Aparecida de Oliveira Duarte (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2012)
Foi avaliado o uso de cinco ou mais medicamentos (polifarmácia) e seus fatores associados por idosos do município de São Paulo. Realizou-se estudo transversal de base populacional: Estudo SABE - Saúde, Bem-estar e Envelhecimento, no ano de 2006. A amostra foi composta por 1.115 idosos com 65 anos e mais, que correspondiam a 422.377 indivíduos do Município de São Paulo. Utilizou-se regressão logística múltipla. A prevalência de polifarmácia foi de 36%. Sexo feminino (OR = 1,7; IC 95%: 1,0; 2,9), idade igual ou superior a 75 anos (OR = 1,9; IC 95%: 1,3; 2,7), maior renda (OR = 1,8; IC 95%: 1,2; 2,8), estar trabalhando (OR = 1,8; IC 95%: 1,1; 2,9), auto avaliação de saúde regular (OR = 1,6; IC 95%: 1,1; 2,3) ou ruim (OR = 2,6; IC 95%: 1,4; 4,9), hipertensão (OR = 2,0; IC 95%: 1,4; 2,9), diabetes (OR = 4,1; IC 95%: 2,2; 7,5), doença reumática (OR = 2,3; IC 95%: 1,5; 3,6) e problemas cardíacos (OR = 2,9; IC 95%: 1,9; 4,5) apresentaram associação positiva com polifarmácia. Usar apenas o sistema público de saúde (OR = 0,5; IC 95%: 0,3; 0,7) associou-se inversamente à polifarmácia. Os medicamentos mais utilizados foram os de ação no sistema cardiovascular e trato alimentar e metabolismo. No âmbito da farmacoepidemiologia, o conhecimento dos fatores associados a polifarmácia, como os identificados nesse estudo, pode ser útil para alertar os profissionais da saúde quanto à importância de identificar e monitorar os grupos de idosos mais vulneráveis a polifarmácia. Polypharmacy for the elderly and associated factors were assessed. A cross-sectional study was conducted using data from the SABE Study (Health, Well-being and Aging), 2006. 1,115 individuals representing 422,377 elderly aged 65 or more, living in São Paulo City, were interviewed. Polypharmacy was defined as the use of five or more medications. A multivariate regression logistics was used. Polypharmacy prevalence was 36%. Female (OR = 1.7; IC 95%: 1.0; 2.9), age over 75 years (OR = 1.9; CI 95%: 1.3; 2.7), higher income (OR = 1.8; CI 95%: 1.2; 2.8), working (OR = 1.8; CI 95%: 1.1; 2.9), regular self assessed health (OR = 1.6; CI 95%: 1.1; 2.3) or poor (OR = 2.6; CI 95%: 1.4; 4.9), hypertension (OR = 2.0; CI 95%: 1.4; 2.9), diabetes (OR = 4.1; CI 95%: 2.2; 7.5), rheumatic diseases (OR = 2.3; CI 95%: 1.5; 3.6) and cardiac problems (OR = 2.9; CI 95%: 1.9; 4.5) were associated positively with polypharmacy. Using only the public health system (OR = 0.5, 95% CI: 0.3; 0.7) was inversely associated with polypharmacy. Medicines for the cardiovascular system and for the alimentary tract and metabolism were the most used. The knowledge of factors associated with polypharmacy, such as those identified in this study, may be useful to alert health professionals about the importance of identifying and monitoring the elderly groups most vulnerable to polypharmacy.